Neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, neutrophil–platelet score and prognostic nutritional index: do they have prognostic significance in metastatic pancreas cancer?. (4th May 2018) - Dogan, Mutlu; Algin, Efnan; Guven, Zeynep Tugba; Baykara, Meltem; Kos, Tugba Fahriye; Bal, Oznur; Zengin, Nurullah
Abstract: Introduction: We aimed to evaluate the prognostic significance of neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), neutrophil–platelet score (NPS) and prognostic nutritional index (PNI) as proinflammatory markers in metastatic pancreas cancer (MPC). Material and methods: A total of 146 MPC patients followed up at our center were evaluated retrospectively for clinicopathological characteristics and hematological ratios (NLR, PLR, NPS and PNI). PNI was calculated as (10 × serum albumin [g/dL]) + (0.005 × peripheral lymphocyte count [per mm³]). Log rank and Cox regression analysis were used. Results: Median age was 53 years (range: 22–78) with male predominance (73.3%). Liver (94.7%) was the most common site for metastasis. Half (53.4%) of the patients had ECOG-PS <2; 18% had cholestasis. Palliative chemotherapy predominantly gemcitabine was given to 86.3% of the patients. Clinical benefit rate was 58.2% and objective response rate (ORR) was 23%. Median overall survival (OS) and progression-free survival (PFS) were 6.3 months (95% CI: 5.2–7.8) and 4.9 months (95% CI: 3.6-6.1). Age ( p = .003), ECOG-PS ( p = .0001), palliative chemotherapy ( p = .002), cholestasis ( p = .001) and NLR ( p = .001) were statistically significant but PLR ( p = .062), NPS ( p = .86) and PNI ( p = .51) were not significant in univariate analysis. Age (HR 1.026, 95% CI: 1.007–1.045, p = .007), ECOG-PS (HR 0.299, 95% CI: 0.202–0.443, p = .0001), cholestasis (HR 0.541, 95% CI: 0.325–0.901, p = .01) and NLR (HR 1.076, 95% CI: 1.025–1.130, p = .003) were significant prognostic factors in multivariate analysis. Conclusions: Basal high NLR (>3), advanced age (>60 years), poor ECOG-PS (>2) and cholestasis were independent poor prognostic factors in MPC. However, PNI, NPS and PLR had no prognostic significance ( p = .51, p = .86 and p = .062, respectively).